Accelerator driven subcritical reactors - Nifenecker, H. (Institute of Physics Pub., 2011)
This book describes the basic knowledge in nuclear, neutron, and reactor physics necessary for understanding the principle and implementation of accelerator driven subcritical nuclear reactors (ADSRs), also known as hybrid reactors.